THE RATE OF BINARY BLACK HOLE MERGERS INFERRED FROM ADVANCED LIGO OBSERVATIONS SURROUNDING GW150914 - Abbott, B. P. (2016)
A transient gravitational-wave signal, GW150914, was identified in the twin Advanced LIGO detectors on 2015 September 2015 at 09: 50: 45 UTC. To assess the implications of this discovery, the detectors remained in operation with unchanged configurations over a period of 39 days around the time of the signal. At the detection statistic threshold corresponding to that observed for GW150914, our search of the 16 days of simultaneous two-detector observational data is estimated to have a false-alarm rate (FAR) of <4.9 x 10(-6) yr(-1), yielding a p-value for GW150914 of <2 x 10(-7). Parameter estimation follow-up on this trigger identifies its source as a binary black hole (BBH) merger with component masses (m(1), m(2)) = (36(-4)(+5), 29(-4)(+4))M-circle dot at redshift z = 0.09(-0.04)(+0.03) (median and 90% credible range). Here, we report on the constraints these observations place on the rate of BBH coalescences. Considering only GW150914, assuming that all BBHs in the universe have the same masses and spins as this event, imposing a search FAR threshold of 1 per 100 years, and assuming that the BBH merger rate is constant in the comoving frame, we infer a 90% credible range of merger rates between 2-53 Gpc(-3) yr(-1)(comoving frame). Incorporating all search triggers that pass a much lower threshold while accounting for the uncertainty in the astrophysical origin of each trigger, we estimate a higher rate, ranging from 13-600 Gpc(-3) yr(-1) depending on assumptions about the BBH mass distribution. All together, our various rate estimates fall in the conservative range 2-600 Gpc(-3) yr(-1).